Optimal location and sizing of thyristor controlled series capacitor using particle swarm optimization technique: article / Mohd Firdaus Yasin - Yasin, Mohd Firdaus (2014)
Transmission loss minimization is a significant issue in Power System (PS). The power loss in Power System could be decreased by installing Flexible AC Transmission System (FACTS) devices. This paper described the application of Particle Swarm Optimization (PSO) for optimal placement and sizing of Thyristor Controlled Series Capacitor (TCSC) to minimize the power loss in the system. PSO is a naturally computational search and optimization technique invented by Eberhart and Kennedy in 1995 which focused on behavior of bird flocking or fish schooling. The objective for this study is to develope a PSO algorithm for loss minimization in power system. The impact of population size and weight coefficient throughout the optimization process is also tested. The technique is tested on IEEE 6 bus system.